A DSL for PIM specifications: design and attribute grammar based implementation - Lukovic, Ivan (2011)
IIS*Case is a model driven software tool that provides information system modeling and prototype generation. It comprises visual and repository based tools for creating various platform independent model (PIM) specifications that are latter transformed into the other, platform specific specifications, and finally to executable programs. Apart from having PIMs stored as repository definitions, we need to have their equivalent representation in the form of a domain specific language. One of the main reasons for this is to allow for checking the formal correctness of PIMs being created. In the paper, we present such a meta-language, named IIS*CDesLang. IIS*CDesLang is specified by an attribute grammar (AG), created under a visual programming environment for AG specifications, named VisualLISA